2019
DOI: 10.1371/journal.pcbi.1007063
|View full text |Cite
|
Sign up to set email alerts
|

Modeling visual performance differences ‘around’ the visual field: A computational observer approach

Abstract: Visual performance depends on polar angle, even when eccentricity is held constant; on many psychophysical tasks observers perform best when stimuli are presented on the horizontal meridian, worst on the upper vertical, and intermediate on the lower vertical meridian. This variation in performance 'around' the visual field can be as pronounced as that of doubling the stimulus eccentricity. The causes of these asymmetries in performance are largely unknown. Some factors in the eye, e.g. cone density, are positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 93 publications
(170 reference statements)
7
67
0
Order By: Relevance
“…Cone density becomes sparser with eccentricity, due to increased size and larger gaps between cones, and decreases by ~30% between the HM and VM at a fixed eccentricity Song et al, 2011). A computational observer model has been used to evaluate the extent to which these optical and retinal factors can explain performance differences in contrast sensitivity with polar angle (Kupers, Carrasco & Winawer, 2019). To account for the 30% increase in contrast sensitivity between the UVM and the HM for stimuli (4 cpd) presented at 4.5º eccentricity (Cameron et al, 2002), the model required an increase by ~7 diopters of defocus or a reduction by 500% in cone density, which exceed by far the variations observed in human eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Cone density becomes sparser with eccentricity, due to increased size and larger gaps between cones, and decreases by ~30% between the HM and VM at a fixed eccentricity Song et al, 2011). A computational observer model has been used to evaluate the extent to which these optical and retinal factors can explain performance differences in contrast sensitivity with polar angle (Kupers, Carrasco & Winawer, 2019). To account for the 30% increase in contrast sensitivity between the UVM and the HM for stimuli (4 cpd) presented at 4.5º eccentricity (Cameron et al, 2002), the model required an increase by ~7 diopters of defocus or a reduction by 500% in cone density, which exceed by far the variations observed in human eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent implementation of a computational observer model has identified that asymmetries in cone sampling and optics can only account for a small portion of isoeccentric differences in contrast sensitivity. Specifically, the model found that a ~30% decrease in contrast sensitivity between the HM and UVM would require a 500% decrease in cone density, which is well beyond the actual density change (Kupers, Carrasco, & Winawer, 2019). Notably, cone densities can vary up by to a factor of 3 across individuals (Curcio, Sloan, Packer, Hendrickson, & Kalina, 1987).…”
Section: Neural Substrates Of Performance Fields Asymmetriesmentioning
confidence: 97%
“…For the main analysis, we use a linear support vector machine (SVM) classifier to discriminate if a stimulus orientation is clockwise or counter-clockwise from vertical given the RGC responses. As in our previous model [46], we apply a 2D fast Fourier transform to the RGC responses at each time point, and remove phase information. Classifying the mRGC amplitudes, rather than the full Fourier representation, allows the inference engine to learn a stimulus template that is robust to small eye movements and stimulus phase, and to categorize the stimulus orientation (illustrated by the high values at the stimulus spatial frequency ( Fig 3 , panel 5).…”
Section: Resultsmentioning
confidence: 99%
“…For comparison with our observer model based on cone outputs in our prior work [46], we used the same simulations as previously (identical eye movement patterns, cone densities, L-, M-, S-cone distributions), and to each of these simulations we added one of five mRGC layers, varying in density and filter widths.…”
Section: Resultsmentioning
confidence: 99%